2016
DOI: 10.1128/aac.00424-16
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Posaconazole Suspension in Lung Transplant Patients with and without Cystic Fibrosis

Abstract: dInvasive fungal infections (IFIs) are common among lung transplant recipients (LTRs). Posaconazole is an important antifungal agent for both prophylaxis and treatment of IFIs; however, detailed pharmacokinetic data are limited among LTRs, particularly those with cystic fibrosis (CF). Our objective was to conduct a pharmacokinetic study of posaconazole oral suspension among LTRs, with particular attention to patients with CF. We enrolled 20 LTRs, 7 with CF and 13 with other underlying lung diseases. Average da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
(23 reference statements)
0
10
1
Order By: Relevance
“…Zhang and colleagues found that LTR with CF had average steady state concentrations 61% lower than non-CF LTR using posaconazole suspension. 30 In reviewing subjects that had concentrations below goal in our study, 36.4% had cystic fibrosis. In the 11 patients with CF, the mean daily dose was 200 mg and mean serum concentration was 1.5 mcg/mL.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Zhang and colleagues found that LTR with CF had average steady state concentrations 61% lower than non-CF LTR using posaconazole suspension. 30 In reviewing subjects that had concentrations below goal in our study, 36.4% had cystic fibrosis. In the 11 patients with CF, the mean daily dose was 200 mg and mean serum concentration was 1.5 mcg/mL.…”
Section: Discussionmentioning
confidence: 78%
“…Fishers exact test was used to compare the proportion of measured serum concentrations reaching a target of ≥0.7 mcg/mL. 30 In reviewing subjects that had concentrations below goal in our study, 36.4% had cystic fibrosis. R version 2.15.3 software was used to analyze data.…”
Section: Discussionmentioning
confidence: 99%
“…As one example, we did not find a significant difference in AUC 0 -24 h or C trough among 7 patients with cystic fibrosis (CF) and 19 patients without CF. In general, patients with CF have increased V and fast clearance (26), and low voriconazole and posaconazole exposures have been documented in this population (27,28). It is also important to recognize that all of our patients were non-Hispanic whites, and all received i.v.…”
Section: Discussionmentioning
confidence: 93%
“…The apparent CL/F observed upon administration of the posaconazole suspension in patients is significantly higher than in healthy volunteers and differs among different patient populations. Patients with persistent febrile neutropenia or refractory IFD, patients from ICU, and cystic fibrosis patients after lung transplantation appear to have high CL/F values (283.0, 195.0 and 143.2 L/h, respectively) [27,36,69], compared with those suffering from AML/MDS/HSCT (42.5-67.0 L/h) [35,37,38]. In general, the difference in F plays an important role in the substantial differences of posaconazole reported absolute clearance with the intravenous formulation and apparent clearance with the oral suspension.…”
Section: Biotransformation and Eliminationmentioning
confidence: 99%
“…As the steady-state trough concentration for posaconazole delayed-release tablet is significantly higher than for the suspension both in cystic fibrosis (CF) (1.1 mg/L vs. 0.19 mg/L) and in non-CF lung transplant patients (1.9 mg/L vs. 0.47 mg/L) [69,148], the delayed-release tablet form is considered a promising alternative to the suspension with satisfactory drug exposure and good tolerance. In lung transplant patients, patients with CF showed significantly lower posaconazole concentrations compared to non-CF patients with both oral formulations [69,148,149], which can increase the risk of subtherapeutic concentration in this subgroup, especially for the suspension.…”
Section: Patients With Cystic Fibrosismentioning
confidence: 99%